Acute effects of whole-body vibration during dynamic lunge movement on jump and sprint performances - Mehmet Kale; Ali Berkay Tolali; Tolga Togram; Umut Davut Basoglu (IP Iermakov S.S., 2024)
Background and Study Aim. The aim of this study was to examine the acute effects of whole-body vibration applied to the dominant and non-dominant leg during repetitive lunge movements on jump and sprint performance. Material and Methods. Thirty-five male students from the Faculty of Sport Sciences voluntarily participated in the study. Participants performed squat jumps and countermovement jumps, and a 30-m sprint test on a non-motorized treadmill as pre- and post-tests. Participants were divided into the experimental group (n = 19, age: 22.0 ± 1.9 years, height: 177.7 ± 6.3 cm, body weight: 75.5 ± 12.6 kg) and the control group (n = 16, age: 21.9 ± 1.9 years, height: 173.4 ± 4.1 cm, body weight: 67.7 ± 7.1 kg). In the experimental group, a whole-body vibration of 50 Hz frequency and 4 mm amplitude was continuously applied to the dominant front leg. This was done on the whole-body vibration platform for 60 seconds throughout the repetitive lunge movement. At the end of the time, the leg was changed, and whole-body vibration was applied to the non-dominant leg using the same method. The control group performed the same movement without whole-body vibration. Pre- and post-test results were compared with an independent sample t-test within the group and a paired sample t-test between the groups. The statistical significance level was determined as p ≤ 0.05. Results. The experimental group showed statistically significant pre-test and post-test differences in 30-m sprint power, non-dominant leg power, and non-dominant leg horizontal force parameters (p < 0.05, p < 0.01, and p < 0.05, respectively). It was determined that performing dynamic lunge movements with the dominant and non-dominant legs using whole-body vibration significantly increased mean power and non-dominant leg horizontal force. Conclusions. The acute effect on power, particularly on non-dominant leg power and non-dominant leg horizontal force during the 30-m sprint, was significant. This showed that whole-body vibration can be used as a short-term training method. In studies aiming to determine the acute and chronic effects of exercises with whole-body vibration on various performance parameters, it is important to focus on the frequency and amplitude differences in certain protocols.